Selecting Indonesia’s Iron and Steel Industry Mitigation Pathways Based on AIM/End-use Assessment - Dewi, Retno Gumilang; Zunita, Megawati; Sevie, Gissa Navira; Kifnasih, Nirma Afrisanti; Syaftika, Novi (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2024)
The measurement of mitigation pathways is important for Indonesia’s iron and steel industry in terms of reducing GHG emissions. This study conducted a cost-effectiveness analysis to assess the economic impacts with associated emission reduction potential of different mitigation strategies by developing an Abatement Cost Curve (ACC) that selects the mitigation option based on the logic of the AIM/End-use model up to 2050. The model was established through the baseline scenario, and the following appropriate mitigation options: adjusting the production structure (CM1), increasing energy efficiency by promoting low carbon technology and non-blast furnace technology that is un-implemented early in modeling years in Indonesia will be included for future reference (CM2), and switching from fossil fuels to low emission fuels (CM3). Results show that the selected technology roadmap from the abatement cost curve below carbon tax 110 US$/tCO2e in 2050 could lead to the most optimal emission reduction of 19.8 MtCO2e, 50.2 MtCO2e, 54.84 MtCO2e with investment costs 93.55 million US$, 1086 million US$, and 1183 million US$ in the scenarios CM1, CM2, and CM3, respectively. The effectiveness of each mitigation action reveals that energy savings and emission reduction from energy will rely mostly on promoting low-carbon technologies. The most effective strategy to reduce emissions from IPPU is to adjust the production structure.